O pedagogo e o Projeto Rondon: relações, interações e contradições na formação inicial - Castro, Maria Eduarda Santos Moreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Rondon's Project represented, in this work, the need of understand on what extent the same provides content and practice that interact or counties with the initial formation in pedagogy. The the theoretical arguments and practices remember to the commitment with the formation of the universitstudentes to the knowledge about the brazilian reality and exercise of citizenship. That way, become a shocking practice, directly in pedagogical training. The relation to this course and the rondon's project are analyzed by means of national curricular guidelines of course of pedagogy, as such, the the readings that follow the Initial Formation of the Pedagogue and Pedagogy as a Social Practice, as well as a study on the aegis of the Rondon Project in Brazilian history. Has haz as general objective to clarify to what extent Project contributes with content and practices in the training of future educators. This is a qualitative study, focusing on Multiple Case studies, with the application of an open questionnaire, to four pedagogues that participated in the Operations of the Rondon Project, with analysis of results based on the triangulation of data between the Rondon Project, Guidelines and Reports of the interviewee. The research concludes that there is a relevance of a set of contents and practices provided by the Rondon Project, that interact, being also possible, being opposed in the formation of the pedagogue

O Projeto Rondon representa, neste Trabalho a necessidade de compreender em que medida o mesmo, propicia conteúdo e práticas que interagem ou se contrapõem à formação inicial em Pedagogia. Os argumentos teóricos e práticas remetem ao comprometimento com a formação dos estudantes universitários para o conhecimento da realidade brasileira e exercício da cidadania. Desse modo, torna-se uma prática que impacta, diretamente, na formação em Pedagogia. A relação desse curso e o Projeto Rondon são analisados, por meio das Diretrizes Curriculares Nacionais do Curso de Pedagogia (2006), como tal, as leituras que sucedem a Formação Inicial do Pedagogo e a Pedagogia como Prática Social e bem como um estudo sobre a égide do Projeto Rondon na história brasileira. Tem como objetivo geral analisar em que medida o Projeto Rondon contribui com conteúdos e prática à formação em Pedagogia. Trata-se de um estudo de natureza qualitativa, com enfoque em estudos de Caso Múltiplos, com a aplicação de um questionário aberto, a quatro pedagogos que participaram das Operações do Projeto Rondon, com análise de resultados baseadas na triangulação de dados entre o Projeto Rondon, Diretrizes e Relatos do entrevistado. A pesquisa concluiu que há uma relevância de um conjunto de conteúdos e práticas proporcionadas pelo Projeto Rondon, que interagem, podendo também, contrapondo-se na formação do pedagogo
Keywords: Projeto Rondon; Educação; Estudantes universitarios; Education